2020
DOI: 10.1002/app.49695
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ammonium persulfate microcapsule with a polyaniline shell and its controlled burst release

Abstract: Polymer hydraulic fracturing is important for increasing production during petroleum exploitation. After fracturing, the high-viscosity polymer should be completely decomposed by gel breakers (ammonium persulfate [APS]) to realize high conductivity in the proppant pack. A new series of polyaniline microcapsules loaded with APS for the preparation of delayed-release gel breakers were synthesized via in situ polymerization. The silica nanoparticles were doped in polyaniline to control the release of the encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The higher the temperature, the faster the dissolution rate of the surface of the capsule. Therefore, the magnitude of the conductivity is controlled by temperature [41]. Capsule-B has a longer delay time than Capsule-A under the same amount of gel-breaker release.…”
Section: Gel-breaking Properties Of Gel Fracturing Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the temperature, the faster the dissolution rate of the surface of the capsule. Therefore, the magnitude of the conductivity is controlled by temperature [41]. Capsule-B has a longer delay time than Capsule-A under the same amount of gel-breaker release.…”
Section: Gel-breaking Properties Of Gel Fracturing Fluidmentioning
confidence: 99%
“…Some tiny cracks appeared on the surface of Capsule-A when the temperature was 60 • C, as shown in Figure 6c, indicating that Capsule-A began to release the gel-breaker at 60 • C. When the temperature increased to 90 • C, there were more cracks on the surface of Capsule-A, as could be seen in Figure 6d, and the width of the cracks was wider, indicating that the release rate of the gel-breaker should be faster at 90 • C. The above conclusions were consistent with those obtained in Figure 5c. The experiment showed that the surface of Capsule-A would generate cracks after being soaked in high-temperature water and then releasing the gel-breaker [41]. It could be seen from the conductivity experiment that Capsule-A and Capsule-B both had the property of delaying the release of the gel-breaker, but the mode of the delaying release needed further research.…”
Section: Gel-breaking Properties Of Gel Fracturing Fluidmentioning
confidence: 99%
“…This polymer has a wide range of application (light-emitting diodes, plastic batteries, switchable membranes, sensors, energy storage devices, anti-static and anti-corrosion coating materials), and has high environmental stability; low cost of the monomer (aniline); high yield easy synthesis; adsorbent properties; as well as modification of mechanical, electromagnetic and solubility properties due to doping acid. 8,9,[14][15][16][17][18] PANI has different oxidation states controlled by oxi-reduction processes, in which protonation and deprotonation occur due to the addition of acids and alkaline solutions. 12,19 Many recent works of Cs/PANI blends carried out the in-situ polymerization of PANI associated with chitosan generating a powder with the ability to adsorb materials such as dyes.…”
Section: Introductionmentioning
confidence: 99%
“…PANI is typically synthesized in a powder form and blended in the polymer matrix as a filler 5 . Aniline (ANI) can not only be in‐situ polymerized in membranes by solvent infusion of the active component but also around APS loaded capsule thus forming a shell of PANI allowing for the delayed slow release of the remaining APS 6 . Another very common approach used is the electro‐polymerization of ANI onto an electrode to produce PANI but it is restricted to electrically conducting substrates found for examples in solar cells or fibers through an interfacial polymerization approach 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Aniline (ANI) can not only be in-situ polymerized in membranes by solvent infusion of the active component but also around APS loaded capsule thus forming a shell of PANI allowing for the delayed slow release of the remaining APS. 6 Another very common approach used is the electro-polymerization of ANI onto an electrode to produce PANI but it is restricted to electrically conducting substrates found for examples in solar cells or fibers through an interfacial polymerization approach. 7,8 Small molecular dopants such as hydrochloric, perchloric, sulfuric, methanesulfonic, benzenesulfonic, p-toluenesulfonic, and macromolecular dopants such as poly(styrene sulfonate (PSS)), poly(vinylsulfonic), poly(acrylic), and poly(anilinesulfonic) acids were used to study the redox properties of PANI.…”
Section: Introductionmentioning
confidence: 99%